The Centrality of Style - Duncan, Mike; M. Vanguri, Star (Open textbook library., 2013)
InThe Centrality of Style, editors Mike Duncan and Star Medzerian Vanguri argue that style is a central concern of composition studies even as they demonstrate that some of the most compelling work in the area has emerged from the margins of the field. Calling attention to this paradox in his foreword to the collection, Paul Butler observes, "Many of the chapters work within the liminal space in which style serves as both a centralizing and decentralizing force in rhetoric and composition. Clearly, the authors and editors have made an invaluable contribution in their collection by exposing the paradoxical nature of a canon that continues to play a vital role in our disciplinary history."